A Review of the Literature on Sexual Assault Perpetrator Characteristics and Behaviors - Greathouse, Sarah Michal (RAND Corporation, 2015)
This report aims to assist the Air Force in its continued efforts to combat sexual assault perpetration within its ranks by examining the existing empirical literature on adult perpetrators who commit sexual assault against other adults, with a particular focus on research published in 2000 or later. The literature search focused on the current state of scientific knowledge and was not limited to studies focusing on military populations.